Omani youth attitudes towards youth programs and their role in protecting them from intellectual and behavioral deviations - Alhaj, Amjad; AL Busafi, Majid; Alzari, Asila; Alkindi, Teeba (Dirasat: Human and Social Sciences, 2022)
The study aims to reveal the reality of youth programs in Oman, its role in protecting from behavioral and thoughts deviation and the most important proposals to activate these programs from their perspectives. It is applied on a sample of (587) females and (390) males, whose ages ranged between 15 and 59 years. An electronic questionnaire is used to collect data that includes two axes: the first is for the primary data of the sample and the program-implementing agency. The second axis contains a scale of (16) which is about the role of youth activities in protecting youth from intellectual and behavioral deviation. In addition to analyzing the content of documents related to youth programs in Oman, the SPSS program is used to analyze the data. It concludes that youth programs have an important role in protecting the thinking and behavior of Omani youth from deviation and it contributes to occupying their free time and directing their energies. The sample responses to the role of programs in protecting youth from intellectual and behavioral deviations do not differ according to their gender or age, but rather according to their educational level and the governorate to which they belong. As it affirms that the individual with higher educational level has the greater awareness, skills and abilities that enable him/her to distinguish between types of thought and behavior. The study recommends that Omani society needs to expand and spread youth programs, and to open official communication channels for youth to contribute in decision-making.